The beautiful soul between duty and effectivity: the Hegelian reading of Iphigenia in Tauris - Paniccia Loureiro Junior, William (Revista Eletrônica Estudos Hegelianos, 2025)
This article analyzes the character Iphigenia in Goethe’s play Iphigenie auf Tauris, proposing that the resolution of the plot—by invoking the ancient Greek laws of hospitality (xenia)—offers a model of reconciliation (Versöhnung) of the beautiful soul (schöne Seele) for Hegel’s Phenomenology of Spirit. In contrast to classical tragedy, conflict resolution in Goethe is expressed through the affirmation of unity between individuals and divine purposes, evoking the code of hospitality as a condition of possibility for the sublation (Aufhebung) of the division between moral duty and its realization. While Euripides’ Iphigenia remains bound to the ethical substance (sittliche Substanz) of spirit’s immediacy, Goethe’s reinterpretation situates the character within the alienated world of culture (Bildung), thus opening the way for the secularized myth to rediscover the divine within the sphere of morality (Moralität), in a key that anticipates, in literary form, the idea of reconciliation present in Hegelian thought.
Keywords: Iphigenia; Goethe; Hegel; Sublation; Beautiful Soul